(untitled) (Damascus University Journal for the economic and Political sciences, 2025)
The current study aimed to identify the role of digital transformation in open innovation by studying the case of Dadoush Clothing Company in Syria, where the study community consisted of all employees in the aforementioned company, and a simple random sample was taken from the community, where the study sample consisted of (90) employees in the company. The questionnaire was used as a main tool in the research to collect data. To achieve this study, the questionnaire was distributed directly to the employees, and then the data was analyzed and the hypotheses were tested using the statistical program (SPSS V.26). The study reached a set of results, including: digital transformation and open innovation are applied in Dadoush Clothing Company. There is also a statistically significant positive effect of digital transformation on open innovation in its studied dimensions (Inbound Open innovation – Outbound Open innovation - Coupled open innovation) in Dadoush Clothing Company. Where the Inbound Open innovation came in the highest degree, indicating that the company is working to bring knowledge and resources from outside to the company; By integrating suppliers, customers, and external knowledge sources, and benefiting from the discoveries of others, it is also open to other companies and establishes relationships with them, which in turn will increase the company’s innovative capacity, as it came after the Coupled open innovation in the second degree, indicating that the company is synthesizing internal and external processes and sharing resources with partners in the company; through alliances with complementary partners, which is a prerequisite for success. While the results of the statistical analysis showed that there is no difference between the average answers of the sample members to the digital transformation variable according to each of (gender, age, job level, experience) in the company studied. A set of proposals were presented, including giving greater priority to investing in digital infrastructure to facilitate open inovation processes more. A set of research ideas were also presented for subsequent studies.